A review of literature on service quality and customer satisfaction of public transport service industry - Jagdish Kanzariya, (National Geographical Journal of India, 2022)
Service quality and customer satisfaction is a most important factor for every economy of the countries. Service quality and customer satisfaction is play vital role for growth and sustains for each business in today global competition. Service quality is defined as quality of service where customer actually expects some quality from service. Customer satisfaction means the person getting support or goods is an outline idea and has to do with such factors as the quality of the product. The quality of the service on condition that the atmosphere of the placing where the product or service is got to own, and the price of the product or service. Customer can satisfy after purchasing product or service if he experience by the same product or service. Customer satisfaction helps to business for profit maximization and cost minimization. Customer satisfaction is also useful to increase level of growth of business and show the way to sustain in the market for long time with profit.